Effectiveness of rotavirus pentavalent vaccine under a universal immunization programme in Israel, 2011–2015: a case–control study. (January 2018) - Muhsen, K.; Anis, E.; Rubinstein, U.; Kassem, E.; Goren, S.; Shulman, L.M.; Ephros, M.; Cohen, D.
Abstract: Objectives: The use of rotavirus pentavalent vaccine (RotaTeq ® ) as a sole vaccine within rotavirus universal immunization programmes remains limited. We examined the effectiveness of RotaTeq in preventing rotavirus gastroenteritis (RVGE) hospitalization in Israel, after the introduction of universal immunization against the disease. Methods: A test-negative case–control study included age-eligible children for universal RotaTeq immunization (aged 2–59 months, born in 2011–2015). Cases ( n  = 98) were patients who tested positive for rotavirus by immunochromatography; those who tested negative ( n  = 628) comprised the control group. Information on rotavirus immunization history was obtained through linkage with a national immunization registry. Vaccination status was compared between cases and controls, adjusted odds ratios (aORs) were obtained from logistic regression models, and vaccine effectiveness calculated as (1 − aOR)*100. Results: Immunization with RotaTeq was less frequent in RVGE cases (73.5%) than in controls (90.1%), p < 0.001; this association persisted after controlling for potential confounders. Effectiveness of the complete vaccine series was estimated at 77% (95% confidence interval (CI): 49–90) in children aged 6–59 months, and 86% (95% CI: 65–94) in children aged 6–23 months; whereas for the incomplete series, the respective estimates were 72% (95% CI: 28–89) and 75% (95% CI: 30–91). Vaccine effectiveness was estimated at 79% (95% CI: 45–92) against G1P[8]-associated RVGE hospitalizations and 69% (95% CI: 11–89) against other genotype-RVGE hospitalizations. Conclusions: High effectiveness of RotaTeq as the sole rotavirus vaccine in a universal immunization programme was demonstrated in a high-income country. Although partial vaccination conferred protection, completing the vaccine series is warranted to maximize the benefit.